A Production systems study on biscuit plant XYZ - Castro, Joseph Michael (College of Engineering, 1994)
This paper is a production systems study of biscuit-making plant. The present system for the continuous production of biscuit X packaged in 3 types is discussed. The manning requirements of the processing and packaging departments are computed by determining and summing up the staffing needs at each step in the process. An analysis of the material handling flow in the preparation of the dough is conducted and a simplified work flow is achieved through a relocation of the raw materials storage area. The individual capacities and utilization of the oven, the creaming and the packaging sections are discussed. How the performance of each section contributes to the overall production output is evaluated. Based on the actual sales of biscuit type X! and X2, a forecast for the first 9 months of 1994, distinct from the forecast supplied by marketing, was generated. A comparison between the forecasts was made, and the suitability of the forecasting technique used by the study group was evaluated. Recommendations concerning employee welfare, plant orderliness and sanitation, facilities and process improvement were listed.